2017
DOI: 10.1007/s00403-017-1760-1
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic analysis of psoriasis identifies the associated metabolites while providing computational models for the monitoring of the disease

Abstract: The majority of studies on psoriasis have focused on explaining the genetic background and its associations with the immune system’s response. The aim of this study was to identify the low-molecular weight compounds contributing to the metabolomic profile of psoriasis and to provide computational models that help with the classification and monitoring of the severity of the disease. We compared the results from targeted and untargeted analyses of patients’ serums with plaque psoriasis to controls. The main dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 59 publications
(54 reference statements)
6
53
0
Order By: Relevance
“…In parallel, the ratio of Orn to Arg in lesional skin was decreased compared to controls suggesting lower arginase activity in PS lesions. The ratio of citrulline to Orn was also lower in PS-L skin compared to PS-NL skin and C being consistent to the lower activity of ornithine carbamoyltransferase found previously in the blood of psoriasis patients 21 . Of note, the levels of citrulline and Orn did not differ significantly between the three groups.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In parallel, the ratio of Orn to Arg in lesional skin was decreased compared to controls suggesting lower arginase activity in PS lesions. The ratio of citrulline to Orn was also lower in PS-L skin compared to PS-NL skin and C being consistent to the lower activity of ornithine carbamoyltransferase found previously in the blood of psoriasis patients 21 . Of note, the levels of citrulline and Orn did not differ significantly between the three groups.…”
Section: Resultssupporting
confidence: 91%
“…In addition Lys is required for biosynthesis of L-carnitine (Car) that was also increased in psoriasis lesions (our data and 20 ). The increase in Glu and Phe levels are well corroborated by the previously found increase of these AAs in the blood of psoriasis patients 21 .…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies showed that altered small molecules metabolism play key roles in the immune dysfunction in autoimmune diseases, including psoriasis, systemic lupus erythematosus, and rheumatoid arthritis [48,49]. In the untargeted metabolomics, employing multivariate statistical analysis, alterations in metabolites that are involved in the IMQ-induced psoriasis were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylcholines (PC) and phosphatidylserine (PS) are the main glycerophospholipids found in the phospholipid membranes [50]. Recent studies revealed that the higher proliferation rates of skin cells could also explain the lower concentrations of PC in psoriasis plasma, which is an essential component of cell membranes [49]. Furthermore, reduced levels of PS were found in active psoriasis [51].…”
Section: Discussionmentioning
confidence: 99%